2022
DOI: 10.1007/s10668-022-02195-9
|View full text |Cite
|
Sign up to set email alerts
|

Honing action competence in sustainable development: what happens in classrooms matters

Abstract: In effectiveness literature, voices are rising to embrace learning contents beyond mathematics, science, and language. Meanwhile, international policy documents such as the United Nations 2019 Climate Action Summit Report point at the importance of action for sustainable development for establishing acceptable life conditions for current and future generations. Therefore, a candidate learning outcome for broadening effectiveness research's scope is action competence in sustainable development (ACiSD), which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…(2021) in that little differences exist in the behaviors of Portuguese students toward suitability in education with respect to age. Similarly, Tuncer (2008) and Sass et al . (2023) found that older individuals appear to be more likely to engage with nature, avoid environmental harm and conserve raw materials and natural resources.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…(2021) in that little differences exist in the behaviors of Portuguese students toward suitability in education with respect to age. Similarly, Tuncer (2008) and Sass et al . (2023) found that older individuals appear to be more likely to engage with nature, avoid environmental harm and conserve raw materials and natural resources.…”
Section: Discussionmentioning
confidence: 64%
“…This finding is aligned with the previous study Aleixo et al (2021) in that little differences exist in the behaviors of Portuguese students toward suitability in education with respect to age. Similarly, Tuncer (2008) and Sass et al (2023) found that older individuals appear to be more likely to engage with nature, avoid environmental harm and conserve raw materials and natural resources. These findings also aligned with our academic classification variable, where our study found that the attitude of senior students toward sustainability in accounting education was statistically different from junior and freshman students.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Integrating action competence into existing courses or developing dedicated courses on sustainability can be challenging within these constraints (Muchira et al , 2023). Besides, achieving action competence in sustainability requires an interdisciplinary approach (Sass et al , 2023), as sustainability challenges are complex and interconnected. However, higher education institutions are often organized into disciplinary silos, making it challenging to foster interdisciplinary collaboration and address sustainability issues holistically (Isac et al , 2022).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Education for Sustainable Development (ESD) or Education for Sustainability (EfS) is a vehicle needed by community members to act in the form of contributing to a sustainable lifestyle and to overcome today's global challenges, including climate change, environmental degradation, consumerism, and so forth (Bascopé et al 2019;Glavič 2020;Paulauskaite-Taraseviciene et al 2022). One way to understand learning in the context of ESD is through the development of action competence (Chen and Liu 2020;Sass et al 2020Sass et al , 2022. Action competence is the competence to act with reference to the environment or the concept of *Corresponding Author: hadi.suwono.fmipa@um.ac.id sustainability (Hedefalk et al 2014;Ideland 2016;Jensen and Schnack 2006;Kalla et al 2022).…”
Section: Introductionmentioning
confidence: 99%